Fibroin-Hybrid Systems: Current Advances in Biomedical Applications - Matheus Valentin Maia; Eryvaldo Sócrates Tabosa do Egito; Anne Sapin-Minet; Daniel Bragança Viana; Ashok Kakkar; Daniel Crístian Ferreira Soares (Molecules)
Fibroin, a protein extracted from silk, offers advantageous properties such as non-immunogenicity, biocompatibility, and ease of surface modification, which have been widely utilized for a variety of biomedical applications. However, in vivo studies have revealed critical challenges, including rapid enzymatic degradation and limited stability. To widen the scope of this natural biomacromolecule, the grafting of polymers onto the protein surface has been advanced as a platform to enhance protein stability and develop smart conjugates. This review article brings into focus applications of fibroin-hybrid systems prepared using chemical modification of the protein with polymers and inorganic compounds. A selection of recent preclinical evaluations of these hybrids is included to highlight the significance of this approach.